Analisis Efisiensi Belanja Fungsi Pendidikan dan Kesehatan Kabupaten/Kota di Pulau Lombok Tahun 2020-2024 - Fajrian Pratama; Siti Sriningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the efficiency of regional spending on education and health functions in districts/cities on Lombok Island during the 2020–2024 period. This study uses a quantitative approach with the output-oriented Data Envelopment Analysis (DEA) method with the assumption of Variable Returns to Scale (VRS). The data used are secondary panel data sourced from the Directorate General of Fiscal Balance, the Central Statistics Agency, and related agencies. The input variables in this study are education and health spending, while the output variables are education and health performance indicators. The results show that in the education sector, all districts/cities on Lombok Island are in the efficient category, although there are differences in the level of consistency of achievement between regions and between years, with Mataram City consistently being on the efficiency frontier. In the health sector, all districts/cities also show a good level of efficiency in managing health spending. This finding shows that the efficiency of regional spending is not only influenced by the size of the budget allocation, but also by the effectiveness of budget management and the quality of policy governance in producing development output achievements. The results of this study are expected to be evaluation material for regional governments in improving the quality of public spending management, especially in the education and health sectors.